1998
DOI: 10.1177/107110079801900306
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Consequences of Sequential Plantar Fascia Release

Abstract: Plantar fascia release has long been a mainstay in the surgical treatment of persistent heel pain, although its effects on the biomechanics of the foot are not well understood. With the use of cadaver specimens and digitized computer programs, the changes in the medial and lateral columns of the foot and in the transverse arch were evaluated after sequential sectioning of the plantar fascia. Complete release of the plantar fascia caused a severe drop in the medial and lateral columns of the foot, compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 12 publications
0
41
1
1
Order By: Relevance
“…It has been proposed that a factor of low MLA was related to plantar aponeurosis [26]. In addition Low FTA was related to plantar aponeurosis [27]. However MLA in this study showed standard range.…”
Section: Discussioncontrasting
confidence: 49%
“…It has been proposed that a factor of low MLA was related to plantar aponeurosis [26]. In addition Low FTA was related to plantar aponeurosis [27]. However MLA in this study showed standard range.…”
Section: Discussioncontrasting
confidence: 49%
“…In a biomechanical study the effect of the plantar release on the medial and lateral column and the plantar was presented [34]. A complete release led to a significant flattening of the structures.…”
Section: Discussionmentioning
confidence: 99%
“…Excision of the medial third fascia is the recommended option because total fascia release impairs the biomechanics of the foot. 33 …”
Section: Discussionmentioning
confidence: 97%